Perspectives on the modern management of non-valvular atrial fi brillation - Gopal, Razeen; Tayebjee, Muzahir H. (SA Heart Journal, 2017)
Atrial fi brillation is the most common clinical arrhythmia. The mainstay in the prevention of atrial fi brillation related stroke is oral anticoagulation. The 2 most important aspects in the management of patients with atrial fi brillation, is therefore risk stratifi cation for stroke and risk assessment for bleeding. Assessment of risk factors is in fact a dynamic process. In appropriate patients, novel anticoagulants are safe and better tolerated, and may be considered as an alternative to warfarin. In patients who are truly intolerant of, or where an absolute contra-indication to anticoagulation exists, occlusion of the left atrial appendage may be considered. Patients are to be carefully counselled with regards this therapy as currently, questions surrounding its safety and long-term effi ciency remain unanswered. This is an area of on-going research and further evidence is awaited. Catheter ablation of atrial fi brillation is a highly effective therapy to achieve freedom of recurrent arrhythmia and relief from symptomatic atrial fi brillation. Recent systematic reviews demonstrate a low incidence of periprocedural complications with regards catheter ablation of atrial fi brillation, with acute complication rates having decreased signifi cantly in recent years. This may be attributed to increasing experience and improved catheter technology.